LINGUOCULTURAL FEATURES OF PHRASEOLOGICAL UNITS IN N.V. GOGOL'S WORK "THE INSPECTOR GENERAL" - Ibodullaeva Shirina Mirzhakhon kizi (Web of Journals Publishing, 2024)
N.V. Gogol's "The Inspector General" serves as a profound satirical commentary on the bureaucratic inefficiencies and moral decay prevalent in Russian society during the early 19th century. The play follows the story of a lowly clerk, Khlestakov, who is mistakenly identified as an important government inspector. This misidentification prompts a series of comedic yet critical encounters with the town's corrupt officials, who are desperate to conceal their misdeeds. Through sharp humor and insightful dialogue, Gogol exposes the absurdity of authority and the pervasive culture of bribery, hypocrisy, and fear. The play not only entertains but also invites reflection on the socio-political landscape of the time, making it a timeless piece that resonates with contemporary issues of governance and morality.
Keywords: phraseological units, linguoculturology, linguistic and cultural identity, cultural concepts, structure and functions of phraseological units, research methodology, intercultural communication, teaching foreign languages.